Wound body and method for producing polyolefin microporous membrane

JP7639340B2Active Publication Date: 2025-03-05TORAY INDUSTRIES INC
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
JP2020536302
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-08-21
Filing Date
2020-06-22
Publication Date
2025-03-05
Estimated Expiration
2040-06-22

AI Technical Summary

Benefits of technology

【0014】 本発明のポリオレフィン微多孔膜は、高空孔率であるにも関わらず、捲回体の巻芯部のような加圧条件においても膜厚の変化率が小さく、且つ、絶縁破壊電圧の高いリチウムイオン二次電池のセパレータを提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007639340000001
    Figure 0007639340000001
  • Figure 0007639340000002
    Figure 0007639340000002
  • Figure 0007639340000003
    Figure 0007639340000003
Patent Text Reader

Abstract

A microporous polyolefin membrane which is characterized by having a thickness of from 16 μm to 30 μm, a porosity of from 40% to 60%, a tortuosity of from 1.00 to 1.42 and a dielectric breakdown voltage of from 155 V / μm to 300 V / μm. A wound body which is characterized by being obtained by winding the microporous polyolefin membrane so as to have an outer diameter of 280 mm or more. The present invention provides a microporous membrane which has a high porosity and a high dielectric breakdown voltage, and which is able to be wound into a wounded body that has a small film thickness difference between the surface layer part and the winding core part even if the wound body has a large diameter.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polyolefin microporous membrane, a polyolefin microporous membrane roll, and a method for producing a microporous membrane. [Background technology]

[0002] Polyolefin microporous membranes (hereinafter sometimes abbreviated as microporous membranes) are used in various fields such as filters such as filtration membranes and dialysis membranes, battery separators, and separators for electrolytic capacitors. Among these, microporous membranes using polyolefin as the resin material have been widely used in recent years as separators for secondary batteries because of their excellent chemical resistance, insulating properties, mechanical strength, and shutdown properties.

[0003] In particular, lithium-ion secondary batteries are widely used in mobile phones, power tools, electric vehicles, etc. As the trend toward higher power and higher capacity continues, there is a demand for lower resistance and lower cost microporous membranes for use as separators. In particular, to achieve high power output, the resistance of the microporous membrane must be low, and the development of microporous membranes with high porosity is required. Furthermore, in order to reduce material switching losses in the microporous membrane manufacturing process, it is predicted that the roll diameter of the wound body will increase due to the increase in the length of the microporous membrane and the increase in the number of turns of the wound body of the microporous membrane that accompanies the increase in length.

[0004] In this specification, a large diameter refers to a diameter of 280 mm or more. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication No. 2018 / 043331 [Patent Document 2] International Publication No. 2015 / 194504 Summary of the Invention [Problem to be solved by the invention]

[0006] However, in the manufacturing process of a large-diameter microporous membrane roll with high porosity, the closer to the core the film is, the higher the internal pressure due to tightening, and the film is compressed, which tends to result in differences in film thickness and porosity between the surface layer and the core.

[0007] For this reason, it is expected that in the future, for high-porosity, large-diameter microporous membrane rolls, there will be an increasing demand for microporous membrane rolls with smaller differences in film thickness and porosity between the surface layer and the core.

[0008] On the other hand, increasing the porosity tends to decrease the dielectric breakdown voltage, making it difficult to achieve both.

[0009] Patent Document 1 discloses a separator that exhibits little change in performance even when electrodes expand and contract, and that exhibits a small rate of change in air permeability resistance when subjected to a compression treatment at a temperature of 60°C, a pressure of 4 MPa, and for 10 minutes. However, the separator has a hybrid structure that has a ladder structure in the submicron region and a three-dimensional mesh structure in the micron region, and does not take into consideration the dielectric breakdown voltage, including areas with large pore diameters.

[0010] Patent Document 2 discloses a separator that has a small rate of change in membrane thickness after compression treatment at a temperature of 90°C and a pressure of 5.0 MPa. However, since the porosity is 40% or less, the membrane has high resistance and performance needs to be improved in order to achieve high output.

[0011] That is, the present invention provides a microporous membrane having a high porosity, a high dielectric breakdown voltage, and a small difference in thickness between the surface layer and the core even in a large-diameter wound body. [Means for solving the problem]

[0012] As a result of extensive investigations aimed at solving the above problems, the present invention was achieved by controlling the fibril structure of a microporous membrane using advanced membrane-forming technology.

[0013] That is, the present invention has the following configuration. (1) A polyolefin microporous film having a thickness of 16 μm or more and 30 μm or less, a porosity of 40% or more and 60% or less, a tortuosity of 1.00 or more and 1.42 or less, and a breakdown voltage of 155 V / μm or more and 300 V / μm or less. (2) The polyolefin microporous membrane according to (1), having an average pore diameter of 20 nm or more and 30 nm or less. (3) A wound body, characterized by being obtained by winding the polyolefin microporous membrane according to (1) or (2) into an outer diameter of 280 mm or more. (4) A method for producing a polyolefin microporous membrane according to (1) or (2), comprising the steps of (a) to (f). (a) a step of melt-kneading and extruding a resin solution containing a polyolefin resin containing 20% ​​by mass or more and 80% by mass or less of ultra-high molecular weight polyethylene and a membrane-forming solvent to obtain an unstretched gel-like sheet; (b) a preheating step of preheating the unstretched gel-like sheet at 95°C or higher and 115°C or lower; (c) a longitudinal stretching step in which the temperature is increased stepwise to a temperature in the range of 1° C. to 15° C. higher than the temperature in the preheating step and the sheet is stretched in the sheet transport direction to obtain a longitudinally stretched sheet; (d) transversely stretching the longitudinally stretched sheet in the sheet width direction at a temperature in the range of 1° C. to 20° C. higher than the temperature in the longitudinal stretching step and at a stretch ratio equal to or higher than that in the longitudinal stretching step to obtain a biaxially stretched sheet; (e) extracting the membrane-forming solvent from the biaxially oriented sheet; (f) after said extracting step, uniaxially stretching said biaxially oriented sheet; Effect of the Invention

[0014] The polyolefin microporous membrane of the present invention has a high porosity, yet exhibits a small rate of change in membrane thickness even under pressurized conditions such as the core part of a wound body, and can provide a separator for a lithium ion secondary battery having a high dielectric breakdown voltage. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] The polyolefin microporous membrane of the present invention will be described below.

[0016] (resin) The polyolefin resin constituting the microporous polyolefin membrane of the present invention is mainly composed of a polyethylene resin. The content of the polyethylene resin is preferably 70% by mass or more, more preferably 80% by mass or more, and even more preferably 100% by mass, based on the total mass of the polyolefin resin being 100% by mass. The polyethylene may be a single substance, but is preferably a polyethylene mixture consisting of two or more types of polyethylene.

[0017] As the polyethylene mixture, at least one selected from the group consisting of ultra-high molecular weight polyethylene, high density polyethylene, medium density polyethylene, branched low density polyethylene, and linear low density polyethylene can be used. The polyethylene may be used alone or in combination of two or more. These can be appropriately selected depending on the purpose of use.

[0018] The polyethylene mixture has a weight average molecular weight (Mw) of 5×10 5 Ultra-high molecular weight polyethylene with Mw of 1×10 or more 4 5×10 or more 5 The following mixtures of polyethylene are preferred. The content of ultra-high molecular weight polyethylene in the polyethylene mixture is preferably 25 to 50% by mass from the viewpoint of film thickness change during compression. The content of ultra-high molecular weight polyethylene in the polyethylene mixture is more preferably 28 to 45% by mass, and even more preferably 30 to 40% by mass. When 25% by mass or more of ultra-high molecular weight polyethylene is present in the polyethylene mixture, the mean flow pore size (through hole size) can be made small, and the rate of film thickness change during compression can be suppressed. In addition, the molecular weight distribution (Mw / Mn (number average molecular weight)) is preferably 1 to 20, more preferably 3 to 10, from the viewpoint of extrusion moldability and physical property control by stable crystallization control.

[0019] (Membrane forming solvent) The membrane-forming solvent is not particularly limited as long as it is a substance that can be mixed with polyolefin resin or dissolve polyolefin resin. Both liquid and solid solvents can be used as the membrane-forming solvent. Examples of liquid solvents include aliphatic or cyclic hydrocarbons such as nonane, decane, decalin, paraxylene, undecane, dodecane, and liquid paraffin, and mineral oil fractions with corresponding boiling points. In order to obtain a gel-like sheet with a stable solvent content, it is preferable to use a non-volatile liquid solvent such as liquid paraffin. The solid solvent preferably has a melting point of 80° C. or less, and examples of such solid solvents include paraffin wax, ceryl alcohol, stearyl alcohol, and dicyclohexyl phthalate. Liquid and solid solvents may be used in combination.

[0020] (Manufacturing method) In the present invention, a polyolefin resin and a membrane-forming solvent are heated, melted and kneaded, the resulting resin solution is extruded through a die and cooled to form an unstretched gel-like sheet, the resulting unstretched gel-like sheet is preheated and then stretched in the machine direction, which is the sheet conveying direction, and then stretched in the transverse direction, which is perpendicular to the conveying direction, to obtain a biaxially stretched sheet, the forming solvent is removed, and the sheet is dried to obtain a microporous membrane. In the case of a simultaneous stretching method in which stretching is performed simultaneously in the machine direction and the transverse direction, it is difficult to provide a stepwise temperature difference during stretching in the machine direction and the transverse direction, so a sequential axial stretching method is preferred to achieve the object of the present invention.

[0021] The method for producing a microporous polyolefin membrane will be specifically described using the sequential stretching method as an example.

[0022] (a) Step for obtaining an unstretched gel-like sheet (Mixing, kneading) A polyolefin solution is prepared by melt-kneading a resin solution containing a polyolefin resin containing 20% ​​by weight or more and 80% by weight or less of ultra-high molecular weight polyethylene and a membrane-forming solvent. The method of melt-kneading the polyolefin resin and the membrane-forming solvent is not particularly limited, but it is preferable to perform the melt-kneading in a twin-screw extruder. The preferred temperature range of the polyolefin solution in the twin-screw extruder varies depending on the resin. For example, the polyethylene composition is 140 to 250°C, and the temperature of the polyolefin solution in the extruder is indirectly grasped by installing a thermometer inside the extruder or on the cylinder, and the heater temperature, rotation speed, and discharge amount of the cylinder are appropriately adjusted to reach the target temperature. The membrane-forming solvent may be added before the start of kneading, or it can be added halfway through kneading. In order to prevent oxidation of the polyolefin resin during melt-kneading, it is preferable to add an antioxidant.

[0023] (Extrusion and Cast) The polyolefin resin solution melted and kneaded in the extruder is cooled to form an unstretched gel-like sheet. For example, the methods disclosed in Japanese Patent No. 2132327 and Japanese Patent No. 3347835 can be used to form the unstretched gel-like sheet.

[0024] The cooling is preferably performed at a rate of 50°C / min or more until the gelation temperature. The cooling is preferably performed to 35°C or less. The microphase of the polyolefin separated by the membrane-forming solvent can be fixed by cooling. If the cooling rate is within the above range, the crystallinity is kept within an appropriate range, and an unstretched gel-like sheet suitable for stretching is obtained. The cooling method can be a method of contacting with a refrigerant such as cold air or cooling water, or a method of contacting with a cooling roll, but it is preferable to cool by contacting with a roll cooled with a refrigerant.

[0025] (b) Preheating process In the preheating step, the unstretched gel-like sheet containing the membrane-forming solvent is gradually heated by passing it through multiple metal rolls until it reaches the longitudinal stretching temperature. Generally, the sheet is preheated by passing it through multiple metal rolls, but rolls coated with ceramic or Teflon (registered trademark) may also be used. By passing through the preheating step, the unstretched gel-like sheet can be stretched without temperature unevenness in the stretching step, and breakage due to uneven physical properties or sudden temperature changes can be suppressed. However, in the present invention, the temperature immediately before entering the longitudinal stretching step in the preheating step is a temperature of -15°C to -1°C lower than the temperature in the longitudinal stretching step, preferably -12°C to -3°C, and more preferably -10°C to -5°C. The temperature obtained by subtracting the temperature in the longitudinal stretching step from the temperature immediately before entering the longitudinal stretching step may be abbreviated as the preheating temperature difference. Specifically, the preheating temperature is in the range of 95°C to 115°C. It is important to provide a temperature difference between the inside and the surface of the gel-like sheet during longitudinal stretching. By subjecting the unstretched gel-like sheet to a preheating process, the pore size in the central part in the thickness direction can be made relatively smaller than that in the surface layer part, and it is possible to improve the breakdown voltage while maintaining a small tortuosity, which are difficult to achieve at the same time.

[0026] (c) Longitudinal stretching process In the longitudinal stretching process, the unstretched gel-like sheet is stretched in the longitudinal direction, so that the polymer chains of the polyolefin are oriented in the stretching direction. The longitudinal stretching process is divided into a stretching process and a heat setting process, and the temperature is adjusted for each process. The longitudinal stretching is performed by passing the sheet through multiple metal rolls with different peripheral speeds. When the unstretched gel-like sheet comes into contact with the first stretching roll in the longitudinal stretching process after passing through the preheating section, it is important to minimize the contact area and contact time with the first stretching roll to adjust the polymer orientation in the surface layer and inner layer.

[0027] The time during which the gel-like sheet is first in contact with the stretching roll after the preheating step is preferably 3 seconds or less, more preferably 2 seconds or less, and even more preferably 1.5 seconds or less. By setting the time within this range, when a membrane-forming solvent with low thermal conductivity such as liquid paraffin is used, the longitudinal stretching can be performed while maintaining a constant temperature difference between the center part and the surface part in the thickness direction.

[0028] It is preferable that the longitudinal stretching is performed in two or more stages, from a low stretching ratio to a high stretching ratio. The stretching ratio in the longitudinal stretching process is preferably 1.1 times or more and 3 times or less, more preferably 1.2 times or more and 2 times or less, because if the temperature of the unstretched gel-like sheet is too low, the stretching stress during longitudinal stretching becomes extremely large and the stretching becomes unstable. The longitudinal stretching ratio in the second stage or later is preferably 1.5 times or less than the previous stage longitudinal stretching ratio, and it is preferable to increase the number of stages to stretch to the desired stretching ratio. By doing so, breakage can be suppressed. The total longitudinal stretching ratio in the longitudinal stretching is preferably 5 times or more and 12 times or less, more preferably 5.5 times or more and 11 times or less. The total longitudinal stretching ratio is the sum of the stretching ratios in each stage. At such a longitudinal stretching ratio, it is easy to obtain a balance between strength and pore size.

[0029] By appropriately adjusting the stretch ratio while maintaining the difference between the preheating temperature and the longitudinal stretching temperature within the above range, it is possible to control the pore opening, reduce the tortuous path length of the microporous membrane, and make the fine pore diameter uniform. In this way, a fibril structure with relatively large pore diameters on the surface and relatively small pore diameters in the center can be obtained, achieving both compression resistance and high dielectric breakdown voltage.

[0030] (d) Step for obtaining a biaxially oriented sheet (lateral stretching process) The longitudinally stretched sheet obtained in the longitudinal stretching step is stretched in the width direction. The transverse stretching is performed by stretching the resulting transversely stretched sheet in a tenter device at a ratio higher than the total longitudinal stretching ratio while holding both ends of the sheet with clips. Specifically, the sheet is preferably stretched at a ratio of 6 to 13, more preferably 6.5 to 12. The transverse stretching temperature is the temperature inside the tenter, and the sheet is stretched at a temperature 1°C to 10°C higher than the longitudinal stretching temperature. The ratios and temperatures of the longitudinal and transverse stretching preferably satisfy the following formulas (a) and (b). (a) Transverse stretch ratio ≧ longitudinal stretch ratio (b) Lateral stretching temperature ≧ Longitudinal stretching temperature

[0031] By satisfying formulas (a) and (b), the transverse stretching process, in which the polymer oriented in the longitudinal direction by longitudinal stretching is stretched in the width direction, is performed at a temperature higher than the longitudinal stretching temperature and at a large stretching ratio, thereby aligning the thicknesses of the fibrils in the longitudinal and transverse directions and maintaining a high dielectric breakdown voltage.

[0032] The difference between the transverse stretching temperature and the longitudinal stretching temperature in formula (b), expressed as transverse stretching temperature - longitudinal stretching temperature, is preferably 1°C or more and 10°C or less, more preferably 3°C or more and 6°C or less.

[0033] (e) Extraction process of membrane-forming solvent The biaxially stretched sheet thus obtained is subjected to extraction of the membrane-forming solvent using a washing solvent. Since the polyolefin phase is phase-separated from the membrane-forming solvent phase, when the membrane-forming solvent is extracted, a porous membrane is obtained that is composed of fibrils that form a fine three-dimensional network structure and has three-dimensionally irregularly connected holes (voids). As the washing solvent and the method for extracting the membrane-forming solvent using the same, a known method can be used. For example, the method disclosed in Japanese Patent No. 2132327 and Japanese Patent Laid-Open Publication No. 2002-256099 can be used.

[0034] (heat fixation) The film from which the membrane-forming solvent has been extracted is subjected to heat treatment in order to stabilize the crystals and make the lamellae uniform.

[0035] Heat setting or heat relaxation can be used as the heat treatment method. Heat setting is a heat treatment in which the membrane is heated while maintaining its dimensions. Heat relaxation is a heat treatment in which the membrane is thermally shrunk in the longitudinal and transverse directions during heating. Heat setting is preferably performed by a tenter method or a roll method. For example, an example of a heat relaxation method is the method disclosed in JP-A-2002-256099. In the heat setting or heat relaxation, the membrane is stretched at least in one axial direction at a ratio of 1.1 to 2 times to increase the strength of the microporous membrane. The microporous membrane is preferably heat treated at a temperature 1°C to 20°C higher than the transverse stretching temperature.

[0036] (winding process) The obtained microporous membrane was wound around an ABS core having an outer diameter of 150 mm to 450 mm at a winding tension of 10 N to 60 N to obtain a jumbo roll. The tension of the jumbo roll is preferably 10 N to 60 N, more preferably 15 N to 55 N. If the winding tension is too low, winding slippage is likely to occur, and if the winding tension is too high, wrinkles and deformation of the film are likely to occur due to tight winding.

[0037] (Slitting process) The microporous membrane wound on the jumbo roll is slit to the desired length and width. In the slitting process, the jumbo roll may be slit to the required width and length in one slit, or may be slit from the jumbo roll in two to four separate slits. The number of slits is preferably five or less, since this increases the probability of foreign matter being mixed in. The slitting tension is adjusted according to the film thickness and width, and is preferably 0.1 N or more and 50 N or less. More preferably, it is 0.5 N or more and 45 N or less, and even more preferably, it is 1.0 N or more and 40 N or less. If the winding tension is too low, winding slippage is likely to occur, and if the winding tension is too high, wrinkles and film deformation are likely to occur due to tight winding.

[0038] (Other processes) The obtained microporous membrane can be provided with layers other than the microporous layer as necessary to form a laminated porous membrane. Examples of the layers include a porous layer formed using a filler-containing resin solution containing a filler and a resin binder or a heat-resistant resin solution.

[0039] (characteristic) The polyolefin microporous membrane of the present embodiment can have high compression resistance and high breakdown voltage while having a high porosity by satisfying the above-mentioned conditions such as the stretching temperature and stretching ratio.

[0040] Hereinafter, each characteristic of the polyolefin microporous membrane of the present embodiment will be described.

[0041] (Film thickness (μm)) The membrane thickness can be measured with a measuring device with a display resolution of up to 0.01 μm. When using a contact type, it is desirable to perform the measurement without crushing the pores of the microporous membrane, and the measurement can be performed with a measuring force of 0.01 N to 0.15 N. The polyolefin microporous membrane is 16 μm to 30 μm, preferably 16 μm to 25 μm. In recent years, batteries have become higher power, and some use thin microporous membranes of 16 μm or less. If the thickness is less than 16 μm, the difference in membrane thickness between the surface layer and the core due to tightening in the manufacturing process is easier to reduce, but coating is often performed to ensure the safety of the battery, and by making the thickness 16 μm or more, a separator that ensures safety can be obtained without performing a coating process. In addition, by making the membrane thickness 30 μm or less, the battery capacity can be ensured and the thickness change between the surface layer and the core of the wound body can be reduced.

[0042] (Porosity (%)) The porosity is defined as the ratio of the volume of the space to the total volume of the substance. Specifically, the thickness and mass of the microporous membrane are measured, and the porosity is calculated using the density of the resin. The density of the resin can be measured according to JIS K 7112:1999. The porosity of the polyolefin microporous membrane is preferably 40% or more and 60% or less. If the porosity is less than 40% when the battery is increased in output, the resistance of the membrane increases, and good output characteristics cannot be obtained when the microporous membrane is used as a battery separator. In addition, if the porosity is 60% or more, the resistance of the membrane is small and good output characteristics can be obtained, but the amount of change in membrane thickness may increase, and if the amount of change in membrane thickness is large, cycle characteristics may deteriorate.

[0043] The porosity is more preferably 45% or more and 55% or less, and further preferably 48% or more and 53% or less.

[0044] (Change in film thickness (%)) The amount of change in film thickness is the amount of change in the core film thickness relative to the surface layer film thickness, and is expressed by the following formula. Amount of change in film thickness (%) = (surface film thickness - core film thickness) / surface film thickness x 100

[0045] The amount of change in film thickness is preferably 0% or more and 0.8% or less, more preferably 0% or more and 0.7% or less, and further preferably 0% or more and 0.6% or less.

[0046] When the amount of change in membrane thickness is within the above range, the number of turns of the microporous membrane in the wound body can be increased in the microporous membrane production process.

[0047] (curvature rate) Tortuosity is the ratio of the thickness of the microporous membrane to the average effective pore path length, and is expressed by the formula Tortuosity = average effective pore path length / membrane thickness. Tortuosity can be measured using a porosimeter. Porosimetry can be performed using either non-mercury porosimetry or mercury porosimetry, but it is preferable to use the non-mercury porosimetry, which does not use harmful mercury.

[0048] The tortuosity is preferably 1.00 or more and 1.42 or less. The lower the tortuosity, the better the compression resistance. More preferably, it is 1.05 or more and 1.40 or less, and even more preferably, it is 1.10 or more and 1.38 or less. If the tortuosity exceeds 1.42, there is a high possibility that the compression resistance will deteriorate. The closer the tortuosity is to 1.00, the better the output characteristics will be, while a higher tortuosity is advantageous in terms of safety, so the above range is preferable in terms of the balance with safety. The tortuosity is measured by the press-in method.

[0049] (Breakdown voltage (V / μm)) The dielectric breakdown voltage can be measured according to JIS C2110-1:2016. The dielectric breakdown voltage per 1 μm of film thickness is preferably 155 V / μm or more and 300 V / μm or less, more preferably 160 V / μm or more and 290 V / μm or less, and even more preferably 165 V / μm or more and 280 V / μm or less. If the dielectric breakdown voltage is 155 V / μm or less, even if discharge occurs due to static electricity, pinholes are unlikely to open in the microporous membrane. Also, if the dielectric breakdown voltage exceeds 300 V / μm, the average pore size of the microporous membrane becomes too small, making it difficult for the electrolyte to penetrate.

[0050] (Average pore diameter (nm)) The average pore size can be measured using a perm porometer. Unlike a porosimeter, a perm porometer can selectively measure the narrowest part of the pores. The average pore size of the polyolefin microporous membrane measured using a perm porometer is preferably 20 nm or more and 30 nm or less, more preferably 22 nm or more and 28 nm or less, and even more preferably 23 nm or more and 27 nm or less. By controlling the pore size of the membrane within the above range, a high dielectric breakdown voltage can be maintained.

[0051] [Measurement method]

[0052] (Measurement of film thickness (μm)) The membrane thickness was measured by cutting a microporous membrane at an arbitrary position to a length of 110 cm in the vertical direction and 6 cm in the horizontal direction to prepare a test piece. The thickness of this test piece was measured at 20 points at 5 cm intervals in the vertical direction using a contact thickness meter, and the average was used to determine the thickness of the test piece. The thickness measuring device used was a Mitsutoyo Litematic VL-50B (with a carbide spherical probe of φ9.5 mm) with a measuring force of 0.01 N. The measurement was performed in an environment of 23±2°C.

[0053] (Measurement of film thickness change rate (%)) A polyolefin microporous membrane slit to a width of 60 mm was wound around an ABS core having an outer diameter of 200 mm and an inner diameter of 76.2 mm until the outer diameter reached 280 mm to obtain a wound body. This polyolefin microporous membrane wound body was stored at 23±2° C. for 2 weeks, and the film thickness was measured at 20 points at 50 mm intervals in the inward direction of the winding, starting from a point 2 m from the surface layer, and the average value was taken as the surface layer film thickness.

[0054] The polyolefin microporous membrane roll was cut open, and the membrane thickness was measured at 20 points at 5 cm intervals from the core starting from a point 10 m away from the core toward the outside of the roll, and the average membrane thickness was recorded as the core membrane thickness. The membrane thickness of the polyolefin microporous membrane was measured 5 minutes after being released from the rolled state. Film thickness change rate (%) = (surface film thickness - core film thickness) / surface film thickness x 100

[0055] (Measurement of porosity (%)) Prepare a 95 mm square sample and measure its volume (cm3 The porosity (%) was calculated from the results obtained by measuring the sample mass (g) and the density (0.99 g / cm3) according to JIS K 7112:1999. 3 was used. Porosity = (1 - sample mass / (resin density x sample volume)) x 100

[0056] (Air permeability resistance (sec / 100cm 3 ) Measurement Using a digital Oken type air resistance tester EGO1 manufactured by Asahi Seiko Co., Ltd., the polyolefin laminated microporous membrane of the present invention was fixed so as not to wrinkle the measurement part, and was measured according to JIS P-8117 (2009). The sample was 5 cm square, the measurement point was one point in the center of the sample, and the measured value was the air resistance [seconds] of the sample. The same measurement was performed on 10 test pieces taken from any film position, and the average value of the 10 measured values ​​was taken as the air resistance of the polyolefin microporous membrane.

[0057] (Measurement of tensile strength (kPa) and tensile elongation (%)) The tensile strength in each direction was measured by cutting a 10 mm wide specimen in accordance with JIS K7127, Type 2, without marking the microporous membrane, at a chuck gap of 20 mm and a test speed of 100 mm / min. The measurement was performed in an environment of 23±2°C.

[0058] (Measurement of curvature ratio) The measurement was performed using purified water using a pure water intrusion porosimeter (product name, model: WIP-3k-A-1) manufactured by POROUS MATERIALS, INC.

[0059] The pore specific volume, specific surface area, porosity, and permeability coefficient of the microporous membrane are measured using a pure water intrusion porosimeter, and the tortuosity is calculated from the formula (a) using the membrane thickness with the contact thickness meter. The membrane was cut into a square of 5 cm in the longitudinal direction and 5 cm in the transverse direction from an arbitrary position to prepare a test piece. The thickness of the test piece was measured at five arbitrary points with a contact thickness meter, and the average was used to determine the thickness of the test piece. The thickness meter used was a Mitsutoyo Litematic VL-50B (with a carbide spherical probe φ9.5 mm) with a measuring force of 0.01 N.

[0060]

number

[0061] l e :Average effective hole length l d : Film thickness ε: Porosity V p : Specific pore volume S BET : specific surface area k: permeability coefficient

[0062] (Measurement of dielectric breakdown voltage (V / μm)) Using a DC withstand voltage tester manufactured by Kasuga Electric Co., Ltd., a voltage of 100 V / sec was applied, and the voltage at which the test piece broke down was measured 20 times. The average value was divided by the film thickness measured with the contact thickness meter described above, and the breakdown voltage was calculated by converting it to a value per 1 μm.

[0063] The upper electrode was a 50g brass cylinder with a diameter of 25mm and a rounded edge of 3mm radius, and the lower electrode was a brass plate. The microporous membrane was cut to 100mm x 100mm, and the lower electrode, microporous membrane, and upper electrode were arranged in this order for measurement.

[0064] (Measurement of average pore diameter (nm)) Measurements were performed in the order of dry-up and wet-up using a Perm Porometer (product name, model: CFP-1500A) manufactured by POROUS MATERIALS, INC. For wet-up, pressure was applied to a microporous membrane thoroughly soaked in Galwick (product name) with a known surface tension, and the pore size calculated from the pressure at which air begins to penetrate was taken as the bubble point pore size (maximum pore size). The average pore size was calculated from the pressure at the point where the curve showing half the slope of the pressure-flow curve in the dry-up measurement intersects with the curve in the wet-up measurement. The following formula was used to convert pressure and pore size. d=C·γ / P

[0065] In the formula, "d (μm)" is the pore size of the microporous membrane, "γ (mN / m)" is the surface tension of the liquid, "P (Pa)" is the pressure, and "C" is a constant.

[0066] (Measurement of weight average molecular weight (Mw)) The Mw of UHMwPE and HDPE was determined by gel permeation chromatography (GPC) under the following conditions. Measurement equipment: Waters Corporation GPC-150C Column: Shodex UT806M manufactured by Showa Denko K.K. Column temperature: 135℃ Solvent (mobile phase): o-dichlorobenzene Solvent flow rate: 1.0 ml / min Sample concentration: 0.1 wt% (dissolution conditions: 135℃ / 1h) Injection volume: 500μl Detector: Waters Corporation differential refractometer (RI detector) Calibration curve: A calibration curve obtained using a monodisperse polystyrene standard sample is converted into a given It was created using.

[0067] Example 1 Mw is 2.0×10 6 Ultra-high molecular weight polyethylene (UHPE) 30% by mass and Mw 5.6 × 10 5High density polyethylene (HDPE: density 0.955g / cm 3 A mixture was prepared by blending 0.2 parts by mass of tetrakis[methylene-3-(3,5-ditertiarybutyl-4-hydroxyphenyl)-propionate]methane as an antioxidant with 100 parts by mass of polyolefin resin consisting of 70% by mass of tertiary butyl ether (melting point 135°C). 28.5 parts by mass of the resulting mixture was put into a strong mixing type twin screw extruder, 71.5 parts by mass of liquid paraffin [35 cSt (40°C)] was fed from the side feeder of the twin screw extruder, and melt-kneaded under conditions of 230°C and 250 rpm to prepare a polyolefin resin solution.

[0068] The polyolefin resin solution was fed from the twin-screw extruder to a T-die, and the extrudate was taken up with a cooling roll whose temperature was adjusted to 30° C. and cooled while being taken up, to form an unstretched gel-like sheet.

[0069] The unstretched gel-like sheet was passed through a preheating roll at 113°C, and then stretched in three steps, 1.3 times, 1.8 times, and 2.4 times, at a total longitudinal stretching ratio of 5.6 times using a longitudinal stretching roll with a diameter of 200 mm at a surface temperature of 119°C, which is 6°C higher than the preheating temperature, before the temperature rose to the inside of the unstretched gel-like sheet. The sheet was then passed through three cooling rolls and cooled to 50°C to form a longitudinally stretched sheet. At this time, the conveying speed was adjusted so that the time during which the unstretched gel-like sheet first came into contact with the longitudinal stretching roll after the preheating step was 2.0 seconds so that the temperature did not rise to the inside.

[0070] Both ends of the obtained longitudinally stretched sheet were held with clips, and the sheet was stretched 8.9 times in the transverse direction using a tenter apparatus set at 125° C. to obtain a biaxially stretched sheet. The obtained biaxially stretched sheet was washed with methylene chloride to extract and remove the remaining liquid paraffin, and then dried.

[0071] The biaxially stretched sheet obtained after drying was heated to 130°C in a tenter type stretching machine, re-stretched to 1.44 times the width of the stretching machine inlet, and then heat-treated to adjust the lateral stretching ratio to 1.31 times the width of the re-stretching device inlet to obtain a polyolefin microporous membrane with a thickness of 19.5 μm. The sheet was slit to a width of 60 mm with a winding tension of 4 N and wound around a resin core with an outer diameter of 203 mm to obtain a wound battery separator with an outer diameter of 303 mm.

[0072] Example 2 Mw is 2.0×10 6 25% by mass of ultra-high molecular weight polyethylene and Mw of 5.6 × 10 5 High density poly workman Styrene (density 0.955g / cm 3 100 parts by mass of polyolefin resin consisting of 75% by mass of tetrakis[methylene-3-(3,5-ditertiarybutyl-4-hydroxyphenyl)-propionate]methane (melting point 135°C) was blended with 0.2 parts by mass of tetrakis[methylene-3-(3,5-ditertiarybutyl-4-hydroxyphenyl)-propionate]methane as an antioxidant to prepare a mixture. 28.5 parts by mass of the obtained mixture was put into a strong mixing type twin screw extruder, 71.5 parts by mass of liquid paraffin [35 cSt (40°C)] was fed from the side feeder of the twin screw extruder, and melt-kneaded under conditions of 230°C and 250 rpm to prepare a polyolefin resin solution. A polyolefin microporous membrane having a thickness of 19.3 μm was obtained in the same manner as in Example 1. Using this polyolefin microporous membrane, a wound body was obtained in the same manner as in Example 1. Using this polyolefin microporous membrane, a wound body was obtained in the same manner as in Example 1.

[0073] Example 3 Mw is 2.0×10 6 Ultra-high molecular weight polyethylene of 40% by mass and Mw of 5.6 × 10 5 High density poly workman Styrene (density 0.955g / cm 3A polyolefin microporous membrane having a thickness of 19.5 μm was obtained in the same manner as in Example 1, except that 0.2 parts by mass of tetrakis[methylene-3-(3,5-ditertiarybutyl-4-hydroxyphenyl)-propionate]methane was blended as an antioxidant into 100 parts by mass of polyolefin resin consisting of 60% by mass of tertiary olefin copolymer (melting point 135° C.) to prepare a mixture. Using this polyolefin microporous membrane, a wound body was obtained in the same manner as in Example 1. Using this polyolefin microporous membrane, a wound body was obtained in the same manner as in Example 1.

[0074] Example 4 The unstretched gel-like sheet of Example 1 was passed through a preheated roll at 115°C and stretched in the longitudinal direction using a longitudinal stretching roll having a diameter of 200 mm at a surface temperature of 119°C, which was 4°C higher than the preheating temperature, in the same manner as in Example 1 to obtain a polyolefin microporous membrane having a thickness of 19.5 μm. Using this polyolefin microporous membrane, a wound body was obtained in the same manner as in Example 1.

[0075] Example 5 The unstretched gel-like sheet of Example 1 was passed through a preheated roll at 109°C and stretched in the longitudinal direction using a longitudinal stretching roll having a diameter of 200 mm at 122°C, which was 13°C higher than the preheating temperature, in the same manner as in Example 1 to obtain a polyolefin microporous membrane having a thickness of 19.6 μm. Using this polyolefin microporous membrane, a wound body was obtained in the same manner as in Example 1.

[0076] Example 6 A polyolefin microporous membrane having a thickness of 19.4 μm was obtained in the same manner as in Example 1, except that the longitudinally stretched sheet of Example 1 was stretched 8.9 times in the transverse direction using a tenter apparatus set at 120° C. A wound body was obtained in the same manner as in Example 1 using this polyolefin microporous membrane.

[0077] Example 7 The unstretched gel-like sheet of Example 1 was passed through a preheat roll at 113°C, and a longitudinal stretching roll with a diameter of 150 mm was used at a surface temperature of 119°C, which is 6°C higher than the preheating temperature. The conveying speed was adjusted so that the time that the unstretched gel-like sheet contacts the longitudinal stretching roll that first contacts after the preheating step is 1.0 seconds, and the sheet was stretched in three steps of 1.3 times, 1.8 times, and 2.4 times in the longitudinal direction at a total longitudinal stretching ratio of 5.62 times. The rest of the procedure was the same as in Example 1, and a polyolefin microporous membrane with a thickness of 19.4 μm was obtained. Using this polyolefin microporous membrane, a roll was obtained in the same manner as in Example 1.

[0078] Example 8 The unstretched gel-like sheet of Example 1 was passed through a preheat roll at 113°C, and a longitudinal stretching roll with a diameter of 250 mm was used at a surface temperature of 119°C, which is 6°C higher than the preheating temperature. The conveying speed was adjusted so that the time that the unstretched gel-like sheet contacts the longitudinal stretching roll that first contacts after the preheating step is 3.0 seconds, and the sheet was stretched in three steps of 1.3 times, 1.8 times, and 2.4 times in the longitudinal direction at a total longitudinal stretching ratio of 5.62 times. The rest of the procedure was the same as in Example 1, and a polyolefin microporous membrane with a thickness of 19.5 μm was obtained. Using this polyolefin microporous membrane, a roll was obtained in the same manner as in Example 1.

[0079] Example 9 The same polyolefin resin solution as in Example 1 was fed from a twin-screw extruder to a T-die, and the extrusion was taken up by a cooling roll adjusted to 30°C, and cooled while being taken up to form an unstretched gel-like sheet. The unstretched gel-like sheet obtained was divided into three stages in the longitudinal direction, 1.8 times, 1.8 times, and 2.4 times, and stretched at a total longitudinal stretching ratio of 7.8 times. A polyolefin microporous membrane having a thickness of 20.0 μm was obtained in the same manner as in Example 1, except that the unstretched gel-like sheet was stretched at a total longitudinal stretching ratio of 7.8 times. Using this polyolefin microporous membrane, a wound body was obtained in the same manner as in Example 1.

[0080] Example 10 The polyolefin resin solution of Example 1 was fed from a twin-screw extruder to a T-die to form an extrusion molded body. The film was taken up on a cooling roll adjusted to 30°C and cooled while being taken up to form an unstretched gel-like sheet with a thickness of 80% of that of Example 1. A polyolefin microporous membrane with a thickness of 16.0 μm was obtained in the same manner as in Example 1 except for the thickness of the unstretched gel-like sheet. Using this polyolefin microporous membrane, a wound body was obtained in the same manner as in Example 1.

[0081] Comparative Example 1 The polyolefin resin solution of Example 1 was fed from the twin-screw extruder to a T-die, and the extrudate was taken up by a cooling roll adjusted to 30°C, and cooled while being taken up to form an unstretched gel-like sheet. The unstretched gel-like sheet obtained was simultaneously stretched 5 times in the longitudinal direction and 5 times in the transverse direction using a tenter device set at 117°C to obtain a biaxially stretched sheet. After obtaining the biaxially stretched sheet, the same procedure as in Example 1 was carried out to obtain a polyolefin microporous membrane having a thickness of 19.5 μm. Using this polyolefin microporous membrane, a wound body was obtained in the same manner as in Example 1.

[0082] Comparative Example 2 Mw is 2.0×10 6 Ultra-high molecular weight polyethylene of 18% by mass and Mw of 5.6 × 10 5 High density polyethylene (density 0.955g / cm 3 100 parts by mass of polyolefin resin consisting of 82% by mass of tetrakis[methylene-3-(3,5-ditertiarybutyl-4-hydroxyphenyl)-propionate]methane (melting point 135°C) was blended with 0.2 parts by mass of tetrakis[methylene-3-(3,5-ditertiarybutyl-4-hydroxyphenyl)-propionate]methane as an antioxidant to prepare a mixture. 30 parts by mass of the obtained mixture was put into a strong kneading type twin screw extruder, 70 parts by mass of liquid paraffin [35 cSt (40°C)] was fed from the side feeder of the twin screw extruder, and melt kneaded under conditions of 230°C and 250 rpm to prepare a polyolefin resin solution in the same manner as in Example 1, and a polyolefin microporous membrane having a thickness of 19.2 μm was obtained in the same manner as in Example 1 except that the mixture was prepared. Using this polyolefin microporous membrane, a wound body was obtained in the same manner as in Example 1.

[0083] Comparative Example 3 The unstretched gel-like sheet of Example 1 was passed through a preheat roll at 119 ° C., and a longitudinal stretching roll with a diameter of 300 mm was used with a surface temperature of 119 ° C., the same as the preheating temperature, in order to sufficiently heat the inside, the conveying speed was adjusted so that the time that the unstretched gel-like sheet contacted the longitudinal stretching roll that it first contacted after the preheating step was 6.0 seconds, and the sheet was stretched in three stages in the longitudinal direction, 1.3 times, 1.8 times, and 2.4 times, with a total stretching ratio of 5.62 times. The rest was the same as in Example 1, and a polyolefin microporous membrane with a thickness of 19.5 μm was obtained. Using this polyolefin microporous membrane, a roll was obtained in the same manner as in Example 1.

[0084] Comparative Example 4 The unstretched gel-like sheet of Example 1 was passed through a preheat roll at 113°C, and stretched in the longitudinal direction at a total stretching ratio of 5.62 times in three stages of 1.3 times, 1.8 times, and 2.4 times at 125°C, which was 12°C higher than the preheat temperature. The sheet was then passed through three cooling rolls and cooled to 50°C to form a longitudinally stretched sheet.

[0085] The obtained longitudinally stretched sheet was held at both ends with clips and stretched 8.9 times in the transverse direction using a tenter device set at 113°C, which was 12°C lower than the longitudinal stretching temperature so that the longitudinal stretching temperature was equal to or higher than the transverse stretching temperature, to obtain a biaxially stretched sheet. The rest of the procedure was the same as in Example 1 to obtain a polyolefin microporous membrane having a thickness of 19.4 μm. Using this polyolefin microporous membrane, a wound body was obtained in the same manner as in Example 1.

[0086] Comparative Example 5 A longitudinally stretched sheet was formed in the same manner as in Example 1, except that the unstretched gel-like sheet of Example 1 was preheated and stretched in the longitudinal direction at a stretching ratio of 1.8 times, 1.8 times, and 2.4 times in three stages, and stretched at a total longitudinal stretching ratio of 7.8 times.

[0087] The obtained longitudinally stretched sheet was held at both ends with clips and stretched 6.8 times in the transverse direction using a tenter device set at 125°C so that the longitudinal stretch ratio was greater than or equal to the transverse stretch ratio, to obtain a biaxially stretched sheet. After obtaining the biaxially stretched sheet, a polyolefin microporous membrane having a thickness of 19.4 μm was obtained in the same manner as in Example 1. Using this polyolefin microporous membrane, a wound body was obtained in the same manner as in Example 1.

[0088] Comparative Example 6 The polyolefin resin solution of Example 1 was fed from a twin-screw extruder to a T-die to form an extrusion molded body. The sheet was taken up on a cooling roll adjusted to 30° C. and cooled while being taken up, to form an unstretched gel-like sheet having a thickness of 60% of that of Example 1.

[0089] The unstretched gel-like sheet was passed through a preheat roll at 113°C, and then stretched in three steps, 1.8 times, 1.8 times, and 2.4 times, at a total longitudinal stretching ratio of 7.8 times using a longitudinal stretching roll with a diameter of 200 mm at a surface temperature of 120°C, which is 7°C higher than the preheating temperature, before the temperature rose to the inside of the unstretched gel-like sheet. The sheet was then passed through three cooling rolls and cooled to 50°C to form a longitudinally stretched sheet. At this time, the conveying speed was adjusted so that the time the unstretched gel-like sheet was in contact with the longitudinal stretching roll that it first came into contact with after the preheating step was 2.0 seconds.

[0090] Both ends of the obtained longitudinally stretched sheet were held with clips, and the sheet was stretched 8.9 times in the transverse direction using a tenter apparatus set at 115° C. to obtain a biaxially stretched sheet. The obtained biaxially stretched sheet was washed with methylene chloride to extract and remove the remaining liquid paraffin, and then dried.

[0091] The biaxially stretched sheet obtained after drying was heated to 130°C in a tenter type stretching machine, re-stretched to 1.44 times the width of the stretching machine inlet, and then heat-treated to adjust the lateral stretching ratio to 1.31 times the width of the re-stretching device inlet to obtain a polyolefin microporous membrane with a thickness of 11.9 μm. The sheet was slit to a width of 60 mm with a winding tension of 3.5 N and wound around a resin core with an outer diameter of 203 mm to obtain a wound battery separator with an outer diameter of 268 mm.

[0092] The blending ratio of each component, production conditions, evaluation results, etc. of the polyolefin microporous membranes obtained in Examples 1 to 10 and Comparative Examples 1 to 6 are shown in Tables 1 to 3.

[0093] [Table 1]

[0094] [Table 2]

[0095] [Table 3]

Claims

1. A winding obtained by winding a polyolefin microporous film whose main component is a polyethylene resin having a thickness of 16 μm or more and 30 μm or less, a porosity of 40% or more and 60% or less, a tortuosity ratio of 1.00 or more and 1.42 or less, and a breakdown voltage of 155 V / μm or more and 300 V / μm or less, around an outer diameter of 280 mm or more, wherein the change in core film thickness relative to the surface layer film thickness of the winding is 0% or more and 0.8% or less.

2. The wound body according to claim 1 , wherein the polyolefin microporous membrane has an average pore diameter of 20 nm or more and 30 nm or less.

3. A method for producing a microporous polyolefin membrane, comprising the steps of (a) to (f). (a) A step of melt-kneading and extruding a resin solution containing a polyolefin resin mainly composed of a polyethylene resin containing 20% ​​by mass or more and 80% by mass or less of ultra-high molecular weight polyethylene and a membrane-forming solvent to obtain an unstretched gel-like sheet. (b) a preheating step of preheating the unstretched gel-like sheet at 95° C. or higher and 115° C. or lower; (c) a longitudinal stretching step in which the temperature is gradually increased to a temperature in the range of 1° C. to 15° C. higher than the temperature in the preheating step and stretched in the sheet transport direction to obtain a longitudinally stretched sheet; (d) A process of transversely stretching the longitudinally stretched sheet in the sheet width direction at a temperature in the range of 1° C. to 20° C. higher than the temperature in the longitudinal stretching process at a stretch ratio equal to or higher than that in the longitudinal stretching process to obtain a biaxially stretched sheet. (e) Extracting the membrane-forming solvent from the biaxially oriented sheet (f) uniaxially stretching the biaxially oriented sheet after the extracting step.

4. 4. The method for producing a polyolefin microporous membrane according to claim 3, wherein the polyolefin microporous membrane has a thickness of 16 μm or more and 30 μm or less, a porosity of 40% or more and 60% or less, a tortuosity of 1.00 or more and 1.42 or less, and a breakdown voltage of 155 V / μm or more and 300 V / μm or less.

5. The wound body according to claim 1 or 2, wherein the polyolefin microporous membrane is made of a polyethylene mixture containing 20% ​​by mass or more and 80% by mass or less of ultra-high molecular weight polyethylene having a weight-average molecular weight of 5 x 10 5 or more, and further containing polyethylene having a weight-average molecular weight of 1 x 10 4 or more and 5 x 10 5 or less.

6. The method for producing a polyolefin microporous membrane described in claim 3 or 4, wherein the polyolefin resin consists of a polyethylene mixture containing 20 mass % or more and 80 mass % or less of ultra-high molecular weight polyethylene having a weight average molecular weight of 5 x 10 5 or more, and further containing polyethylene having a weight average molecular weight of 1 x 10 4 or more and 5 x 10 5 or less.

Citation Information

Patent Citations

  • Polyolefin-made laminated microporous film

    JP2015208893A

  • Polyolefin-made laminated microporous film

    JP2015208894A

  • Manufacturing method of battery separator and wound body of battery separator

    JP2016143640A

  • Polyolefin microporous membrane

    JP2019143008A

  • Microporous membrane wound body and method of manufacturing it

    JP2020093927A